Pengaruh Minyak Atsiri Asal Kulit Jeruk Manis dan Besar terhadap Perkembangan Tungau Panonychus citri (Acarina: Tetranychidae) - Mizu lstianto; Kasumbogo Untung; Y. Andi Trisyono; Triwibowo Yuwono (Jurnal Perlindungan Tanaman Indonesia, 2003)
P. citri (Acarina: Tetranychidae) is one of the economically important citrus pests in Indonesia. However, the association of this pest with its host is not well understood. The objective of this research was to evaluate the effects of essential oil extracted from sweet orange and pumello fruit peels on the development of P. citri. The research was conducted in the laboratory of IP2TP Tlekung Malang, using a complete random design consisted of six treatments. Fifteen mites were used for each treatment. The treatments were concentrations 10, 20, 40, and 80 ppm of essential oil. Parafin was used as a positive control because it was a diluting solution for the essential oil. The control received no application. The result showed that the main content of essential oil extracted from sweet orange and pumello was limonene. The essential oils prolonged the life cycle and reduced the fecundity of P. citri. The effects of essential oil extracted from pumello were found to be more pronounced than were from sweet orange. These differences might be due to the differences in the composition of the volatile compounds other than limonene.